2019
DOI: 10.1002/ece3.5267
|View full text |Cite
|
Sign up to set email alerts
|

Macroevolution of arboreality in salamanders

Abstract: Evolutionary theory predicts that selection in distinct microhabitats generates correlations between morphological and ecological traits, and may increase both phenotypic and taxonomic diversity. However, some microhabitats exert unique selective pressures that act as a restraining force on macroevolutionary patterns of diversification. In this study, we use phylogenetic comparative methods to investigate the evolutionary outcomes of inhabiting the arboreal microhabitat in salamanders. We find that arboreality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 57 publications
2
39
0
Order By: Relevance
“…Furthermore, because the shift between foraging in water and in terrestrial environments is abrupt, we suggest that the morphological changes occurred quickly to adapt to new sensorial and physiological environments. Indeed, vertebrates can evolve faster when they are confronted with rapid environmental modifications (56)(57)(58). The consistent (17 times) and highly convergent loss of olfactory capacities and the gain of thermoregulatory capacities at the order level is surprising.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because the shift between foraging in water and in terrestrial environments is abrupt, we suggest that the morphological changes occurred quickly to adapt to new sensorial and physiological environments. Indeed, vertebrates can evolve faster when they are confronted with rapid environmental modifications (56)(57)(58). The consistent (17 times) and highly convergent loss of olfactory capacities and the gain of thermoregulatory capacities at the order level is surprising.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we presented strong evidence of a morphological response to ecological selective pressures in a family of salamanders whose morphology is not often associated with differences in habitat (Kozak and Wiens 2016). Previous investigations into the macroevolution of morphology have largely concluded that variation in plethodontid body proportions across taxa do not always correspond to what is predicted by selection across environmental gradients (Adams et al 2009;Blankers et al 2012;Baken andAdams 2019, but see Bonett andBlair 2017). The uniquely compelling results of our study suggest that SA:V may represent a key morphological trait that does respond predictably to environmental selective pressures, as much of the physiology of plethodontids, and thus their organismal performance, is mitigated through the consequences of cutaneous respiration and possible desiccation risk (see Feder 1983).…”
Section: Discussionmentioning
confidence: 70%
“…; Blankers et al. ; Baken and Adams , but see Bonett and Blair ). The uniquely compelling results of our study suggest that SA:V may represent a key morphological trait that does respond predictably to environmental selective pressures, as much of the physiology of plethodontids, and thus their organismal performance, is mitigated through the consequences of cutaneous respiration and possible desiccation risk (see Feder ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations